Study of Acoustic Parameters of Audible and Visual Warning Devices Used by the Police of the Czech Republic - Fiserova, Svetla; Hrinko, Martin (Communications - Scientific letters of the University of Zilina, 2012)
In the article, the authors are concerned with acoustic parameters of audible and visual warning devices used by the Police of the Czech Republic. The objective of the article is, in context with the fundamental rules of sound and its propagation in environments and with associated health risks, to describe in accordance with valid legislative requirements the acoustic parameters of audible and visual warning devices used by the Police of the Czech Republic. Results of the acoustic study, their evaluation and recommendations for their field use will be presented.